Involvement of toll-like receptors 3 and 7/8 in the neuropathogenesis of bovine herpesvirus types 1 and 5 - Rensetti, Daniel Ernesto; Marin, Maia Solange; Quintana, Silvina; Morán, Pedro Edgardo; Verna, Andrea Elizabeth; Odeon, Anselmo Carlos; Perez, Sandra (Elsevier, 2019)
Bovine herpesvirus types 1 (BoHV-1) and 5 (BoHV-5) are closely related alpha-herpesviruses. BoHV-5 is the causal agent of non-suppurative meningoencephalitis in calves. BoHV-1 causes respiratory disease, abortions, genital disorders and, occasionally, encephalitis in cattle. Both viruses are neurotropic and they share similar biological properties. Nevertheless, they differ in their ability to cause neurological disease. Toll-like receptors (TLRs) are involved in the innate immune response to pathogens. In this study, the variations in the expression levels of TLRs were evaluated in different regions of the bovine central nervous system during the acute infection and reactivation of BoHV-1 and BoHV-5- infected cattle. With the exception of TLR9, significant up-regulation of all TLRs was detected following primary infection of neural tissues by both bovine alpha-herpesviruses. Furthermore, the stages of acute infection and reactivation were characterized by a distinguishable TLR expression pattern. Important differences in TLR expression upon infection of the central nervous system by BoHV-1 or BoHV-5 were not detected. The striking differences in TLR mRNA levels during acute infection and reactivation provide evidence that the innate immune response may be involved in the clinical outcomes observed at each stage. Further research is required to analyze the mechanisms that initiate TLR activation and the signaling cascade mediated by each TLR to elucidate the precise role these receptors play in bovine herpesvirus encephalitis.